Localized modulus-controlled PDMS substrate for 2D&3D stretchable electronics - Miao, Liming; Guo, Hang; Ji Wan; Wang, Haobin; Yu Song; Chen, Haotian; Chen, Xuexian; Haixia (Alice) Zhang (Journal of Micromechanics and Microengineering, 2019)
Stretchable electronics have great importance in the application of wearable device and electronic skin. The balance and improvements of mechanical stretchability and electronic performance are the great challenges that restrict the further development of stretchable electronics. In order to achieve stretchable electronics, it is crucial to choose the proper substrates, among which PDMS is the most commonly used polymer due its easy fabrication and low cost. In this paper, we propose a novel strategy and fabricate localized and precise modulus-controlled PDMS for both two/three-dimensional stretchable electronics. Based on a secondary cross-link effect, the modulus of cured PDMS can be enhanced and precisely controlled by spin-coating different mass of curing agent. Using laser-cutted PI mask, the modulus-enhanced region can be defined by users. Through this simple method, the functional conductive thin-film materials (Gold/Ag nanowires/Reduced Graphene oxide) can be well protected when the structural layer is stretched and the “Barrel Effect” of multi-materials film (different material films possess different stretchability) on one piece of substrate can also be solved. Besides, the localizedly modified PDMS as a substrate can form different 3D buckling structures on it by pre-stretching and releasing process compared with uniform PDMS, which shows a new way to control the 3D buckling structure.